Morphological and Biometrical Features of the Maxilla in Mongrel Dogs (Canis Lupus Familiaris) - Priya Pachauri; Archana Pathak; M. M. Farooqui; Rupam Sinha; Varsha Gupta (Indian Journal of Veterinary Anatomy, 2026)
This study examines the morphology and biometry of the maxilla bone in Mongrel dogs based onanalyses of 14 specimens. The maxilla, the largest facial bone, is paired and located laterally, forming parts of thenasal cavity, hard palate, and orbital region. It features an irregularly triangular body with concave rostral andconvex caudal facial surfaces, a frontal process fitting between nasal and frontal bones, a short zygomaticprocess, and a palatine process contributing 64.6±0.67% to the hard palate alongside the premaxilla. The alveolarprocess holds the canine teeth, four premolars, and two molars. An infraorbital foramen is located 1 cm above thethird cheek tooth. The Present findings align, provides a baseline for comparative studies and clinical applicationsin dental and maxillofacial procedures.